One‐Pot Synthesis of Cobalt‐Doped Pt–Au Alloy Nanoparticles Supported on Ultrathin α‐Co(OH)2 Nanosheets and Their Enhanced Performance in the Reduction of p‐Nitrophenol. Issue 1 (14th December 2016) - Long, Yan; Li, Jian; Wu, Lanlan; Li, Junqi; Wang, Xiao; Yao, Shuang; Song, Shuyan; Zhang, Hongjie
Abstract : Cobalt‐doped Pt–Au alloy nanoparticles with a narrow size distribution and small sizes of ca. 4 nm were deposited on ultrathin α‐Co(OH)2 nanosheets through a one‐pot method. The whole process could be divided into two steps: coreduction by NaBH4 and subsequent partial oxidation by air. The compositions of the as‐prepared y ‐Pt x Au100– x /Co(OH)2 ( x = 0, 25, 50, 75, 100, y = 1 %, 10 %) materials can be accurately controlled by adjusting the amounts of the raw materials. The structure of y ‐Pt x Au100– x /Co(OH)2 was affected by the doped cobalt. The effects of ultrathin α‐Co(OH)2 nanosheets and the chemical composition of Pt x Au100– x NPs on the catalytic activity for the reduction of 4‐nitrophenol (4‐NP) were investigated systematically. 1 %‐Pt50 Au50 /Co(OH)2 exhibits the most significantly enhanced catalytic activity. Its much higher activity than those of 1 %‐Pt/Co(OH)2, 1 %‐Au/Co(OH)2, and a physical mixture of Pt50 Au50 nanoparticles and ultrathin α‐Co(OH)2 nanosheets suggests that there is a synergy between the Pt and Au and between the Pt x Au100– x nanoparticles and the supports. Abstract : Cobalt‐doped Pt–Au alloy nanoparticles with a narrow size distribution and small sizes of ca. 4 nm are deposited on ultrathin α‐Co(OH)2 nanosheets through a one‐pot method to give y ‐Pt x Au100– x /Co(OH)2 nanocomposites. The nanocomposites show excellent catalytic activity and stability for the reduction of 4‐nitrophenol with low noble‐metal loading (1 %).